PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN KONSUMEN MEMBELI MOTOR KAWASAKI NINJA 250CC DI KOTA PALU - PANJILI, FAHRI (Fakultas Ekonomi Universitas Tadulako, 2018)
The purpose of this study is to determine the effect of product quality consisting of Performance, Features, Reliability, Durability, Ease of Repair and Aesthetics of customer satisfaction buy Kawasaki Ninja 250cc motorcycle in Palu City. The method used in this research is descriptive method causal with the number of samples 32. Methods of respondents with accidental sampling technique and multiple linear regression analysis with the help of SPSS for Windows release 16.0. The results of this study indicate that: (1) Product quality variables consisting of Performance, Features, Reliability, Ease of repair, and Aesthetics simultaneously affect the decision of consumers to buy Kawasaki Ninja 250cc Motorcycles in Palu City; (2) Variable product quality consisting of Performance, Feature, Ease of repair, and Aesthetics in Persial effect on consumer decision to buy Kawasaki Ninja 250cc Motorcycle in Palu City. However, the Variable Reliability does not significantly influence the consumer's decision to buy a 250cc Ninja Kawasaki Motorcycle in Palu City.